Evaluación de la colonización del hongo Pleurotus ostreatus en sustratos lignocelulósicos (2021)
Expanded polystyrene is characterized by being a material used as packaging material that requires long periods of degradation, generating high rates of contamination for terrestrial and aquifer ecosystems, which is why the need arises to formulate alternative and biodegradable materials that can replace the use of said material. Therefore, throughout the development of this document, a colonization protocol will be sought that allows the development of a biomaterial based on Pleurotus ostreatus fungal mycelium, a microorganism that is characterized by being a microorganism with an enzymatic machinery that allows it to degrade compounds lignocellulosics, which allows their expansion and growth along the study substrates which are wheat bran and coffee husk, which is the most polluting residue generated in coffee production, is due to its high percentages of lignified compounds, thus giving way to the growth and implementation of a circular economy.